1986
DOI: 10.1002/bip.360251006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple denaturational transitions in fibrillar collagen

Abstract: SynopsisThe heat denaturation of pepsinized bovine nonfibrillar and fibrillar collagen was studied by differential scanning calorimetry. For fibrillar preparations that had been rapidly precipitated with stirring at low ionic strength, then resuspended a t physiological ionic strength, multiple denaturational transitions were observed. At heating rates of 10"C/min, melting endotherms occurred a t about 44,50,53, and 57OC. Fibrillar collagen that was slowly gelled without stirring a t physiological ionic streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…Equation (4) Figure 1 shows the temperature dependence of specific heat capacity (C p ) of the collagen in acetic acid at different heating rates. As reported before, 15,16 at any heating rate, a bimodal transition with a major peak at T m $ 408C and a shoulder at T s $ 328C are observed. As the heating rate increases from 0.5 to 1.338C/min, both of them shift to higher temperatures, indicating that they involve kinetic effect.…”
Section: Laser Light Scatteringsupporting
confidence: 59%
See 3 more Smart Citations
“…Equation (4) Figure 1 shows the temperature dependence of specific heat capacity (C p ) of the collagen in acetic acid at different heating rates. As reported before, 15,16 at any heating rate, a bimodal transition with a major peak at T m $ 408C and a shoulder at T s $ 328C are observed. As the heating rate increases from 0.5 to 1.338C/min, both of them shift to higher temperatures, indicating that they involve kinetic effect.…”
Section: Laser Light Scatteringsupporting
confidence: 59%
“…It has been suggested that collagen forms several distinct fibrillar species, and each of them has a characteristic melting temperature. 16 Since all the species consist of the same collagen molecules, it is impossible that some species have a reversible melting but the others have an irreversible one. The reversibility of the shoulder transition indicates that it is not due to the denaturation of a certain collagen species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wallace et a/. 31 ) suggested that the very thin fibrils from an acid soluble collagen solution denaturated below 50°C, consistent with our finding. McPherson et al 32 l recognized that the addition of heparin to collagen fibrillar suspensions promotes the growth in fibril diameter and make fibrils grow to a higher stability on DSC.…”
Section: Thermal Denaturation Behavior Of Recon-supporting
confidence: 92%